Effect of Thiobacillus thioparus 1904 and sulphur addition on odour emission during aerobic composting. (February 2018) - Gu, Wenjie; Sun, Wen; Lu, Yusheng; Li, Xia; Xu, Peizhi; Xie, Kaizhi; Sun, Lili; Wu, Hangtao
Highlights: Addition of sulphur controls compost ammonia emissions but increases VSCs emissions. Addition of Thiobacillus thioparus effectively controls VSCs emissions. Combined use of sulphur and T. thioparus effectively controls both ammonia and VSCs. Abstract: The effects of sulphur and Thiobacillus thioparus 1904 on odour emissions during composting were studied. Results indicated that the sulphur addition reduced the pH and decreased cumulative emission of ammonia and the nitrogen loss by 47.80% and 44.23%, respectively, but the amount of volatile sulphur compounds (VSCs) and the sulphur loss increased. The addition of T. thioparus 1904 effectively reduced the cumulative emissions of H2 S, methyl sulphide, methanethiol, dimethyl disulphide and the sulphur loss by 33.24%, 81.24%, 32.70%, 54.22% and 54.24%, respectively. T. thioparus 1904 also limited the nitrogen loss. The combined application of sulphur and T. thioparus 1904 resulted in the greatest amount of nitrogen retention. The accumulation of ammonia emissions was reduced by 63.33%, and the nitrogen loss was reduced by 71.93%. The combined treatment did not increase the emission of VSCs. The application of sulphur and T. thioparus 1904 may help to control the odour of compost.